Dual-market tourism system collapse: A system dynamics analysis of how international tourist pricing exploitation destroys local tourism through cross-market contagion - Olivar, Gladies Mae C. (Edelweiss Applied Science and Technology, 2025)
This paper examines unregulated pricing practices targeting foreign tourists, revealing that local tourism markets suffer more severe damage than international markets through cross-market contagion mechanisms. Using integrated system dynamics and agent-based modeling validated with 92% accuracy against documented tourism crises, we analyze dual-market interactions under unregulated pricing scenarios over 10-year periods. Our simulation results reveal that local tourism arrivals decline by 76% compared to 44% for international tourism, with local satisfaction collapsing by 82% versus 63% for international visitors. Community support falls to 20%, and cultural authenticity drops to 32%, indicating a fundamental breakdown in sustainability. Recovery of local tourism requires 2-3 times longer than international recovery (15-35 versus 8-15 years) due to the need to rebuild community relationships. The study introduces cross-market contagion theory through three novel feedback loops: exploitation-reputation spiral, local tourism displacement loop, and cultural commodification accelerator. Policy intervention analysis demonstrates that integrated dual-market approaches achieve superior outcomes, with local tourism showing a 179% improvement under transparency measures compared to 39% for international tourism. These findings challenge traditional tourism economics by positioning local tourism as the foundational stability mechanism for destination competitiveness. The research establishes that effective pricing policies must explicitly protect both international and local market segments simultaneously.